2005
DOI: 10.1007/s10072-005-0427-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation and cluster headache

Abstract: In recent years, neuroimaging data have greatly improved the knowledge on trigeminal autonomic cephalalgias' (TACs) central mechanisms. Positron emission tomography studies have shown that the posterior inferior hypothalamic grey matter is activated during cluster headache attacks as well as in short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT). Voxel-based morphometric MRI has also documented alteration in the same area in cluster headache patients. These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 8 publications
0
25
0
5
Order By: Relevance
“…Nevertheless, targeting the hypothalamus with DBS has already been shown to be safe and potentially effective in managing patients with intractable chronic cluster headache. 61 Furthermore, stereotactic electrocoagulation of the LH in obese hu mans was performed safely more than 30 years ago, resulting in significant, although transient, appetite suppression and slight weight reduction in 3 patients. 90 Given this evidence, it was recently proposed that chronic bilateral DBS of the LH at high frequencies would mimic the results of lesion studies, just as STN DBS for PD mirrors the effect of subthalamotomy.…”
Section: 105mentioning
confidence: 99%
“…Nevertheless, targeting the hypothalamus with DBS has already been shown to be safe and potentially effective in managing patients with intractable chronic cluster headache. 61 Furthermore, stereotactic electrocoagulation of the LH in obese hu mans was performed safely more than 30 years ago, resulting in significant, although transient, appetite suppression and slight weight reduction in 3 patients. 90 Given this evidence, it was recently proposed that chronic bilateral DBS of the LH at high frequencies would mimic the results of lesion studies, just as STN DBS for PD mirrors the effect of subthalamotomy.…”
Section: 105mentioning
confidence: 99%
“…In the current single patient study we took advantage of the fact that the PIH has been identified recently as a promising target for the treatment of cluster headache (Bartsch et al, 2008;Bussone et al, 2007;Leone et al, 2005) and investigated the hypothalamic response to basic motivational stimuli by recording from electrodes placed for DBS treatment. Importantly, and in accord with our expectations, we observed changes in the averaged LFP as a function of stimulus category.…”
Section: Discussionmentioning
confidence: 99%
“…59 Unfortunately, some safety concerns remain. 60 These concerns have made us explore a new approach to reach these areas of the brain.…”
Section: Safety Issuesmentioning
confidence: 99%